CLOPIDOGREL–INDUCED CHOLESTASIS: A CASE REPORT AND REVIEW OF THE LITERATURE. : Pharmaceutical Sciences-Pharmacology - IBRAHEEM SOMAILI, MOHAMMED; YOUSUF, MUHAMMAD; SALIH, SALIH BIN; ALMANSOUR, SHAHAD (International Journal of Life Science and Pharma Research, 2018)
Clopidogrel is a highly effective antiplatelet agent and is widely used in atherosclerotic vascular diseases especially after cardiac catheterization and percutaneous coronary intervention. Although it appears to be very safe, it may be associated with hepatotoxicity. A 74-year-old male was admitted with anorexia and jaundice. His previous history was significant for hypertension, dyslipidemia, and ischemic heart disease. He had had percutaneous coronary intervention five months previously after presenting with non-ST-elevation myocardial infarction and since then was on dual antiplatelet agents including clopidogrel and aspirin. His other medications included valsartan, atorvastatin, and metoprolol. He was icteric without other positive findings on clinical examination. Extensive investigations suggested cholestasis due to clopidogrel after excluding other causes. Laboratory tests revealed total bilirubin 373.6 μmol/L; direct bilirubin 334 μmol/L; alanine aminotransferase (ALT) 91 IU/L; aspartate aminotransferase (AST) 83 IU/L; alkaline phosphatase (ALP) 978 IU/L, and gamma glutamyl-transferase (GGT) 454 IU/L. The liver profile was normal 5 months earlier. A liver biopsy confirmed pure cholestatic picture. While the patient was waiting for a liver biopsy, his antiplatelet medications were put on hold leading to improvement in cholestasis. Resumption of the clopidogrel after liver biopsy again led to worsening of the cholestasis. On discontinuation of the clopidogrel, jaundice and liver function tests recovered completely within 10 days. Liver function test remained normal on a follow-up review 2 months after the patient was discharged, despite resuming the high-intensity statin dose. Clopidogrel-induced hepatotoxicity is a rare but serious side effect. With increasing use of clopidogrel, all physicians prescribing this medication need to be aware of its’ potential to cause hepatotoxicity including cholestasis. The hepatotoxicity associated with clopidogrel is reversible on early discontinuation of this medication.